E-139 Endovascular treatment of anterior cranial fossa fistulas: the significance of retrograde transvenous approach. (4th August 2020) - Mejia, J; Gutierrez, J; Vargas, O; Torres, V; Patiño, M; Pabon, B
Abstract : Purpose: Anterior cranial fossa (ACF) Dural arteriovenous fistulae (DAVFs) are infrequent lesions, and usually treated by surgical disconnection or endovascular embolization via the ophthalmic artery. The retrograde transvenous route is a rarely used approach. This paper describes our experience in terms of safety and efficacy of embolization of DAVF of the anterior cranial fossa with different embolic agents through the venous side. Materials and Methods: Between September 2016 and January 2020 a retrospective review was performed. A total of 10 patients with DAVF of the anterior cranial fossa managed with embolization through the venous side with Onyx/PHIL were selected. Information on demography, symptoms and signs, angiographic examinations, interventional treatments, angiographic and clinical results, and follow-up was collected and analyzed. Results: Nine patients were included in this study, patients were between 14 and 79 years old (mean 45.6). Six primarily presented with intracranial hemorrhage. All fistulas were fed by the bilateral ethmoidal arteries arising from the ophthalmic artery and by the anterior branch of the middle meningeal artery. One case with history of type D CCF. The abnormal shunt drained into the superior sagittal sinus with interposition of the cortical veins in all nine patients. All of the cases had high-grade Cognard classifications (III-IV). 4(44%) patients had been treated via trans arterial embolization (TAE) via the AEA of the OA. All cases were treated via transvenous embolization (TVE), 8 of 9 (88%) were treated with the trans-SSS approach. Complete angiographic cure was achieved in all patients, without postprocedural complications. There were nearly no symptoms among the patients during follow-up. Conclusion: Embolization of DAVF of the anterior cranial fossa via retrograde using transvenous approach with embolic agents is safe, effective, and a good choice for management of this rare condition. Endovascular treatment (EVT) can completely obliterate the fistula point and correct the venous shunting. More cases are needed to verify these findings. Disclosures: J. Mejia: None. J. Gutierrez: None. O. Vargas: None. V. Torres: None. M. Patiño: None. B. Pabon: None.